Knowledge Enhancement in a Web Learning Environment - Henry Praherdhiono; Ayami Nakaya; Taufik Ikhsan Slamet; Nunung Nindigraha (Teknologi Pendidikan ID, 2025)
This research is motivated by the limitations of time, cost, and energy in facilitating post-training learning. This research aims to develop a web-based knowledge management system design as a supplement to post-training independent learning. Application development adopts the SECI (Socialization, Externalization, Combination, and Internalization) model. The system will record data used as an indicator of decision-making, material presentation, and automatic recommendations for each participant. The method used in this study uses the Davidson-Shiver, Rasmussen, and Lowenthal development model which consists of 1) Analysis, 2) Evaluation Plan, 3) Simultaneous Design which includes design, system development, testing, limited implementation and formative evaluation. 4) Full Implementation, and 5) Summative Evaluation and Research. There are 2 data analysis techniques, qualitative data analysis to measure the accuracy of utilization procedures; and quantitative data analysis to measure technical quality in the form of media validity and learning outcomes.